THE EFFECT OF PERCEIVED OF EASE OF USE, PERCEIVED OF BENEFITS, TRUST, PERCEIVED OF RISK AND LEVEL OF UNDERSTANDING OF ELECTRONIC MONEY ON INTEREST IN USING E-MONEY - Asep Kurniawan; Fenty Yulianti; Trisandi Eka Putri (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2022)
This study aims to determine the effect of perceived ease of use, perceived benefits, trust, perceived risk and level of understanding of electronic money on interest in using e-money. The data used in this study is primary data by distributing questionnaires in the form of google from. The population in this study were accounting students throughout West Java. The sample in this study amounted to 300 people. The method used in sampling is non-probability sampling method using purposive sampling technique. This study uses a quantitative approach. Data analysis was performed using SPSS version 22. The results showed that in particular the perceived ease of use variable had a positive effect on interest in using e-money. The perceived benefit variable has a positive effect on asking to use e-money. Trust variable has a positive effect on interest in using e-money. The risk perception variable does not have a positive effect on interest in using e-money and the level of understanding has a positive effect on interest in using e-money. Simultaneously, the research results show that the variables of perceived ease of use, perceived benefits, trust, risk perception and level of understanding of electronic money affect the interest in using e-money among accounting students in West Java.